Bone repair material based on usnic acid, glycerophosphoric acid and sulfuric acid salt and preparation method thereof
By combining salts of pineoxylic acid, glycerol phosphoric acid and sulfuric acid in bone repair materials, and combining calcium, magnesium, strontium, zinc and iron, the degradation rate of existing bone repair materials is not matched with the osteogenesis rate and lack of antibacterial inhibition in bone repair materials. The problem of inflammation function has achieved effective repair and reconstruction of bone tissue and reduced the occurrence of surgical complications.
Patent Information
- Application Number
- CN202411296558.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-24
AI Technical Summary
The degradation rate of existing bone repair materials does not match the osteogenesis rate, cannot be completely degraded into bone tissue, and lacks antibacterial and anti-inflammatory functions, resulting in poor surgical complications and repair results.
Designed a bone repair material based on salts of pineoxylic acid, glycerol phosphoric acid and sulfuric acid, containing slowly dissolved pineoxylic acid, moderately degraded glycerol phosphate and rapidly solidified sulfate, combining calcium, magnesium, strontium, zinc and other elements, which have antibacterial, anti-inflammatory and promote wound healing.
This material can gradually degrade at bone tissue contact, provide early support and gradual reconstruction functions, reduce surgical complications, promote bone tissue repair and reconstruction, and the degradation rate can match the bone tissue regeneration and reconstruction process, and has full degradation, antibacterial and inflammation-resistant Features.
Smart Images

Figure BDA0005046205360000065 
Figure BDA0005046205360000071 
Figure BDA0005046205360000072
Abstract
Description
Technical Field
[0001] The invention relates to a bone repair material based on a salt of usnic acid, glycerophosphoric acid and sulfuric acid and a preparation method thereof, belonging to the field of bone repair materials. Background Art
[0002] Due to the bone tissue damage caused by traffic accidents, sports and accidents, bone tumor removal caused by lesions, deformation of cervical and thoracic vertebrae caused by long-term sitting and bad habits, as well as necrosis, damage and loss of function of bone tissue caused by various factors such as aging, a large amount of biomaterials are needed as bone tissue repair and replacement to support and maintain normal physiological functions of the human body. At present, the best materials that can fully meet the requirements of bone tissue regeneration and reconstruction are still autologous bone and allogeneic bone. Among them, the source of autologous bone is very small and cannot meet the demand. The use of allogeneic bone has become the most effective treatment method, making bone tissue repair and reconstruction materials with excellent performance one of the core products in the bone repair market. Therefore, the research and development of materials with degradation cycles consistent with the bone repair and reconstruction cycle, certain biomechanical strength, and good osteogenic properties are still urgent tasks.
[0003] However, although there are many materials for studying bone repair and reconstruction, there are only a handful of materials used for clinical treatment in actual application and treatment. Currently, the most studied are the phosphate series represented by hydroxyapatite. This type of product has poor degradation, cannot be completely absorbed by human bone tissue, and cannot complete bone reconstruction. Another type is calcium-silicon bone repair materials represented by calcium silicate, which have good biocompatibility, but cannot be completely absorbed by bone tissue in the body; biomechanics is one of the decisive factors for the function of bone repair materials and repaired tissues. In the past, ceramic materials and metal materials often cause stress shielding due to the great difference in mechanical strength, hardness, stiffness and elastic modulus with bone tissue, which often leads to problems such as loosening of repair materials, wear and necrosis of bone tissue, and separation.
[0004] Moreover, during the operation, the surgical site will be accompanied by various complications such as bacterial infection and inflammation, such as redness, swelling, exudation, etc., which directly affect the repair of bone tissue and wound healing. This requires that the implanted bone repair body should not only be able to promote bone tissue repair, degradation and conversion into bone tissue, but also have antibacterial and anti-inflammatory functions to prevent complications. At present, there are very few products on the market that can be completely converted into bone tissue and promote the rapid regeneration and healing of bone tissue, let alone have antibacterial and anti-inflammatory functions; at most, some antibiotics are mixed into the implant. This mixed drug is a physical mixture, and the implant is only a carrier, and does not have the antibacterial and anti-inflammatory functions to complete the entire repair and reconstruction.
[0005] On the other hand, with the improvement of orthopedic surgical methods and techniques, higher requirements have been placed on surgical methods for bone repair and reconstruction. Traditional open-intestine and large-trauma surgeries are increasingly being resisted by patients. Minimally invasive surgeries with small trauma areas and short duration are the development trend of treatment methods for bone repair and reconstruction.
[0006] Therefore, there is a need in the art for improved bone repair materials to overcome the defects of current bone repair and reconstruction products, such as large differences between degradation rate and osteogenesis rate, inability to completely degrade and transform into bone tissue, or lack of antibacterial and anti-inflammatory functions. Summary of the invention
[0007] In order to solve the above problems, the present invention is based on the origin and formation process of bone tissue, and designs a composite bone tissue repair and reconstruction material containing natural usnic acid salt with slow solubility and degradability, glycerophosphate with moderate degradation rate, and sulfate with calcium source and rapid solidification, so as to overcome the defects of current bone repair and reconstruction products such as large difference between degradation rate and osteogenesis rate, or inability to completely degrade and transform into bone tissue, or lack of antibacterial and anti-inflammatory functions.
[0008] Specifically, in one aspect, the present invention provides a bone repair material based on a salt of usnic acid, glycerophosphate and sulfate, comprising component A, component B and component C.
[0009] The component A is a composite salt of usnic acid, calcium, and optionally other trace metal elements that promote bone tissue regeneration or are required by the human body.
[0010] The component B is a composite salt of glycerophosphate, calcium, and optionally other trace metal elements that promote bone tissue regeneration or are required by the human body.
[0011] The component C is a composite salt of sulfuric acid, calcium, and optionally other trace metal elements that promote bone tissue regeneration or are required by the human body.
[0012] Furthermore, the mass ratio of component A, component B and component C is 10-30:40-50:30-40.
[0013] Furthermore, the molar ratio of calcium element to other trace metal elements in component A is 80-90:10-20.
[0014] Furthermore, the other trace metal elements in component A include at least one of magnesium, strontium, zinc and iron.
[0015] Further, when component A contains calcium, magnesium, zinc and iron elements, the molar ratio of calcium, magnesium, zinc and iron in component A is 80-90:10-5:5-3:5-2.
[0016] Furthermore, the molar ratio of calcium element to other trace metal elements in component B is 80-90:10-20.
[0017] Further, the other trace metal elements in component B do not include magnesium, and preferably include at least one of strontium, zinc and iron;
[0018] Furthermore, the molar ratio of calcium to other trace metal elements in component C is 95-100:0-5;
[0019] Furthermore, the other trace metal elements in component C do not include magnesium, zinc and iron, and preferably include strontium.
[0020] In another aspect, the present invention provides a bone cement based on usnic acid, glycerophosphate and sulfate, comprising a bone repair material based on usnic acid, glycerophosphate and sulfate as described herein and a curing liquid at a solid-liquid ratio of 1.0:0.2-1.5 (g:ml).
[0021] Furthermore, the bone cement can be directly injected into a desired wound or defect site through an injection device, or can be loaded into a mold to be made into a test sample or molded into a desired shape.
[0022] Furthermore, the solidifying liquid is selected from at least one of water for injection, physiological saline or glucose injection.
[0023] In another aspect, the present invention provides a method for preparing the bone repair material based on the salt of usnic acid, glycerophosphate and sulfate as described herein, comprising the following steps:
[0024] (1) firstly reacting usnic acid with a strong base to prepare soluble usnic acid salt, and then reacting the obtained soluble usnic acid salt with calcium and optionally soluble salts of other trace metal elements that promote bone tissue regeneration or are required by the human body to obtain the component A;
[0025] (2) reacting glycerophosphate with calcium and optionally carbonates, oxides and / or hydroxides of other trace metal elements that promote bone tissue regeneration or are required by the human body to obtain the component B;
[0026] (3) reacting sulfuric acid with calcium and optionally carbonates, oxides and / or hydroxides of other trace metal elements that promote bone tissue regeneration or are required by the human body to obtain the component C;
[0027] (4) Component A, component B and component C are mixed and then ball-milled to obtain the bone repair material based on the salt of usnic acid, glycerophosphate and sulfuric acid.
[0028] Furthermore, the molar ratio of the strong base to usnic acid in step (1) is 2.0-2.5:1.0.
[0029] Furthermore, the strong base includes at least one of lithium hydroxide, sodium hydroxide and potassium hydroxide.
[0030] Furthermore, in step (1), the molar ratio of the calcium element and optionally the soluble salt of other trace metal elements that promote bone tissue regeneration or are required by the human body to the soluble usnic acid salt is 1.0-2.0:1.0.
[0031] Furthermore, the molar ratio of calcium to other trace metal elements in the soluble salt of calcium and optionally other trace metal elements that promote bone tissue regeneration or are required by the human body is 80-90:10-20.
[0032] Furthermore, the other trace metal elements promoting bone tissue regeneration or required by the human body in step (1) include at least one of magnesium, strontium, zinc and iron.
[0033] Furthermore, the molar ratio of calcium, zinc, strontium and iron in the soluble salt of calcium and optionally other trace metal elements that promote bone tissue regeneration or are required by the human body is: 80-90:10-5:5-3:5-2.
[0034] Furthermore, the calcium element and optionally the soluble salt of other trace metal elements that promote bone tissue regeneration or are required by the human body in step (1) include at least one of calcium nitrate, magnesium nitrate, strontium nitrate, zinc nitrate, iron nitrate, calcium chloride, magnesium chloride, strontium chloride, zinc chloride, iron chloride, magnesium sulfate, zinc sulfate, and iron sulfate.
[0035] Furthermore, step (1) comprises stirring usnic acid and a strong base in water at 50-80°C for 0.5-2h, then adding an aqueous solution of calcium and optionally a soluble salt of other trace metal elements that promote bone tissue regeneration or are required by the human body, and stirring at 50-80°C for 0.5-2h, then sealing and aging for 12-24 hours, centrifuging the precipitate, and obtaining component A after washing, drying and crushing.
[0036] Furthermore, in step (1), mixing usnic acid and a strong base in water comprises first preparing the strong base into a 1-2M aqueous solution and then adding usnic acid.
[0037] Furthermore, the concentration of the aqueous solution of calcium and optionally soluble salts of other trace metal elements that promote bone tissue regeneration or are required by the human body is 1.0-2.0M.
[0038] Furthermore, in step (2), the molar ratio of calcium to other trace metal elements in the carbonate, oxide and / or hydroxide of the calcium element and optionally other trace metal elements that promote bone tissue regeneration or are required by the human body is 80-90:20-10.
[0039] Furthermore, the other trace metal elements that promote bone tissue regeneration or are required by the human body in step (2) do not include magnesium, and preferably include at least one of strontium, zinc and iron.
[0040] Furthermore, the calcium element and optionally the carbonate, oxide and / or hydroxide of other trace metal elements that promote bone tissue regeneration or are required by the human body in step (2) include at least one of calcium carbonate, strontium carbonate, zinc carbonate, iron carbonate, calcium oxide, strontium oxide, zinc oxide, ferric oxide, calcium hydroxide, strontium hydroxide, zinc hydroxide and iron hydroxide;
[0041] Furthermore, step (2) comprises dissolving glycerophosphate in water, and then adding calcium and optionally carbonates, oxides and / or hydroxides of other trace metal elements that promote bone tissue regeneration or are required by the human body under stirring until the pH of the solution reaches 7.0-7.5, stirring for 1-3 hours, and then sealing and aging for 12-24 hours, centrifuging and separating the precipitate, washing, drying and crushing to obtain the component B.
[0042] Furthermore, in step (2), the concentration of the glycerophosphate solution obtained by dissolving glycerophosphate in water is 1.0-2.0M.
[0043] Furthermore, in step (3), the molar ratio of calcium to other trace metal elements in the carbonate, oxide and / or hydroxide of the calcium element and optionally other trace metal elements that promote bone tissue regeneration or are required by the human body is 95-100:0-5.
[0044] Furthermore, in step (3), the other trace metal element that promotes bone tissue regeneration or is required by the human body is strontium.
[0045] Furthermore, the calcium element in step (3) and optionally carbonates, oxides and / or hydroxides of other trace metal elements that promote bone tissue regeneration or are required by the human body include at least one of calcium carbonate, strontium carbonate, calcium oxide, strontium oxide, calcium hydroxide and strontium hydroxide.
[0046] Furthermore, step (3) comprises preparing a 1.0-2.0 M aqueous sulfuric acid solution, and then adding calcium and optionally carbonates, oxides and / or hydroxides of other trace metal elements that promote bone tissue regeneration or are required by the human body under stirring until the pH of the solution reaches 5.5-6.0, stirring for 1-3 hours, and then sealing and aging for 12-24 hours, centrifuging and separating the precipitate, washing, drying, steaming and crushing to obtain the component B.
[0047] Furthermore, the water vapor treatment is carried out in water vapor at 120-150° C. and 0.2-1 MPa for 3-12 hours.
[0048] Furthermore, in step (4), the mass ratio of component A, component B and component C is 10-30:40-50:30-40.
[0049] Furthermore, the ball milling in step (4) is carried out under nitrogen protection, the temperature of the ball milling chamber is not higher than 60° C., the rotation speed is 200-300 r / hr, and the ball milling time is 2-8 hours.
[0050] Furthermore, step (4) comprises ball milling and then sieving to obtain the bone repair material based on the salt of usnic acid, glycerophosphate and sulfuric acid with a particle size of less than 100 μm.
[0051] Furthermore, the method also includes mixing and blending the bone repair material based on the salt of usnic acid, glycerophosphate and sulfuric acid obtained in step (4) with a solidifying liquid at a solid-liquid ratio of 1.0:0.2-1.5 (g:ml) to obtain bone cement, which can be directly used for injection into the desired trauma or defect site through an injection device, or can be loaded into a mold to make a test sample or molded into a desired shape.
[0052] Furthermore, the solidifying liquid is selected from at least one of water for injection, physiological saline or glucose injection.
[0053] Beneficial effects of the present invention:
[0054] The bone repair material based on the salt of usnic acid, glycerophosphate and sulfuric acid provided by the present invention contains a usnic acid composite salt with slow solubility and degradability, a glycerophosphate composite salt with good solubility and degradability, and a sulfuric acid composite salt with rapid curing ability. The bone repair material based on the salt of usnic acid, glycerophosphate and sulfuric acid has osteogenic elements calcium, phosphorus and trace elements that promote bone tissue formation, has self-solidification, pH neutrality, and full degradation, has antibacterial, anti-inflammatory and wound healing functions, can gradually degrade from the side in contact with the bone tissue, provide components in the whole process of bone tissue repair and reconstruction from the wound surface, and promote tissue repair and reconstruction. The strength after curing has the function of early vacancy support, gradual degradation and tissue fusion, and absorption and replacement by tissue. At the same time, it can provide a variety of organic and inorganic components that promote bone tissue regeneration, improve the regeneration and reconstruction function of the tissue; its degradation rate can be controlled according to the composition and matched with bone tissue regeneration and reconstruction. During use, it can reduce surgical infections caused by bacterial infection and inflammation such as redness, swelling, and exudation, and can be widely used in the repair and reconstruction of bone trauma and defects. DETAILED DESCRIPTION
[0055] In order to provide an improved bone repair material to overcome the defects of existing bone repair and reconstruction products, such as large difference between degradation rate and bone formation rate, inability to completely degrade and transform into bone tissue, or lack of antibacterial and anti-inflammatory functions, the present invention first selects (1) natural usnic acid As one of the core components of bone tissue repair materials, the special functions and therapeutic effects of hemostasis, antibacterial, anti-inflammatory, wound healing, and strengthening human immunity are utilized to enhance the function of the repair material, so that it can avoid bacterial infection, reduce inflammation, reduce bleeding, and accelerate tissue repair and wound healing during the surgical process and subsequent recovery, repair and reconstruction process; the present invention further selects glycerophosphoric acid As another core component of bone tissue repair materials, the salts formed by them have moderate dissolution and degradation properties, and give full play to the different dissolution and degradation properties of calcium salts, strontium salts, zinc salts, iron salts, etc., as well as the different functions in the process of bone tissue formation, repair and reconstruction to regulate the degradation properties of materials, the role of osteoblasts and osteoclasts, and accelerate the repair and reconstruction of bone tissue; in addition, sulfuric acid is selected Calcium salts and strontium salts serve as osteogenic element donors and rapid solidification molding components, providing a calcium source for bone repair and reconstruction materials for immediate shaping, 3D printing, and supporting strength.
[0056] Among them, the optional osteogenic metal elements are calcium, magnesium, strontium, zinc and iron, as well as other beneficial metal elements. According to the content analysis of natural bone elements, excessive rare earth elements are prevented from causing bone cell poisoning and hindering the growth and repair and reconstruction of bone tissue. The present invention uses calcium as the main metal element and magnesium, strontium, zinc and iron as trace elements to form usnic acid glycerophosphate sulfate composite salt bone repair material. In order to achieve the above goals, the present invention will provide the following specific technical routes:
[0057] (1) Preparation of usnic acid salt: The present invention adopts the method of reacting usnic acid with sodium hydroxide solution (as an example) to form sodium usnic acid ( (sodium usnic acid) solution, and then react with soluble calcium, magnesium, strontium and zinc salt solutions to form usnic acid complex salt precipitation The preparation reaction can be schematically shown as follows:
[0058]
[0059]
[0060] The ratio of calcium, magnesium, zinc and iron (mol) is: 80-90:10-5:5-3:5-2. That is, calcium is the main bone-forming element, and other elements are trace elements to improve the bone formation process and promote the bone formation speed.
[0061] (2) Preparation of glycerophosphate complex salt: In the present invention, a slightly excessive amount of carbonate, oxide or hydroxide of calcium, strontium and iron is reacted with glycerophosphate to form glycerophosphate. This type of glycerophosphate has a relatively moderate solubility and can provide calcium and other metal elements for bone formation as well as sufficient phosphorus for bone tissue. The reaction diagram is as follows:
[0062]
[0063] The pH is controlled at 7.0-7.5 as the end point of the complex salt formation. The form of glycerophosphate is: (Calcium glycerophosphate), (strontium glycerophosphate), (zinc glycerophosphate), (Glycerol phosphate iron), etc. Magnesium glycerophosphate has a high solubility in water (79g / L) and is easily lost during washing and centrifugation. Therefore, magnesium glycerophosphate cannot be used as a composite salt component in the present invention, and magnesium is provided by magnesium usnic acid. The ratio (mol) of calcium and other elements (zinc, strontium and iron) is: 80-90:10-20.
[0064] (3) Preparation and treatment of sulfate. The present invention uses high-purity dilute sulfuric acid (1-2M) and carbonates, oxides or hydroxides of calcium and strontium to react to prepare sulfate complex salts, which can be schematically represented as: H2SO4+M1Z+M2Z→M1SO4.M2SO4. M1 and M2 are elements such as calcium and strontium. The pH of MSO4 formed by the reaction is generally lower than 6.0 in water, so pH 6.0 is used as the end point of the reaction. The content of SrSO4 is 0-5% (mol) of MSO4, preferably 1-5% (mol). Zinc sulfate, magnesium sulfate and iron sulfate have a large solubility and will be lost during washing and centrifugation. They cannot be used as sulfate complex salt components to form bone repair materials. The prepared MSO4 needs to be hydrothermally treated to form a hydrate containing half of the crystal water. In the subsequent hydration process, it quickly undergoes a hydration reaction with water, resulting in a solidification effect, so that each component is quickly solidified and formed through the hydration effect, and has a certain biomechanical strength in a relatively short time, providing support before and in the early stage of bone tissue formation.
[0065] (4) According to the functions of each component, the ratio of usnic acid salt to glycerophosphate and sulfate is (wt) 10-30:40-50:30-40. Among them, the role of usnic acid salt is mainly to provide metal elements for bone formation, and to use its special functions and therapeutic effects such as hemostasis, antibacterial, anti-inflammatory, wound healing, and strengthening human immunity. It has an effect on fibroblasts and promotes wound healing, produces chemotaxis on repair cells and inflammatory cells, promotes the migration of repair cells and the deposition of extracellular matrix, and promotes wound healing. In addition to providing phosphorus, the main element of bone formation, glycerophosphate complex salt plays a biological and physiological role of calcium, has the function of improving tissue cells and forming bone tissue, and at the same time plays a role in the metabolism of glycerophosphate calcium salt, which has the function of supplementing brain vitality. In addition to providing calcium and trace element strontium for bone formation, sulfate complex salts also have the characteristics of rapid solidification and shaping through their semi-aqueous molecular structure, which reacts with water to form dihydrates. This allows the prepared bone repair material based on salts of usnic acid, glycerophosphate and sulfuric acid to be able to be quickly plasticized and shaped in the presence of water, saline and glucose solution, providing simple surgical methods and means for minimally invasive surgery and filling of irregular wounds.
[0066] In another aspect, the present invention provides a processing and molding technology and application of a bone repair material based on a salt of usnic acid, glycerophosphate and sulfuric acid. The above-mentioned bone repair material powder based on a salt of usnic acid, glycerophosphate and sulfuric acid is mixed with pure water (water for injection), physiological saline or glucose injection according to a solid-liquid ratio of 1.0:0.2-1.5 (g:ml) and mixed evenly: (1) directly injected into the desired wound or defect site by direct injection; (2) loaded into a mold to make a test sample or molded into a desired shape, naturally solidified and sterilized for use.
[0067] Further, the present invention also includes the performance research and evaluation of the mold as described herein made into a test sample or shaped into a desired shape. The mold as described herein is made into a test sample or shaped into a desired shape, and the molding, degradation, mechanical and biological performance evaluation is performed to obtain the performance related to safety and non-toxicity, full degradation, high activity, easy shaping, etc., and the in vitro performance test of promoting bone tissue repair and reconstruction and being completely replaced by bone tissue during bone tissue repair and reconstruction is performed.
[0068] The loading mold as described in this article is made into a test sample or molded into a desired shape and implanted into the back of New Zealand white rabbits according to the requirements of T16886 to observe its biosafety such as degradation and inflammation in vivo.
[0069] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0070] Example 1
[0071] (1) Preparation of usnic acid complex salt: 82 g of sodium hydroxide was dissolved in 2 L of deionized water, and after stirring until completely dissolved, 344 g of usnic acid was added, and the temperature was gradually raised to 60° C. while stirring until completely dissolved, to form a transparent usnic acid sodium salt solution. The soluble usnic acid solution obtained above was directly used as a raw material for preparing usnic acid complex salt.
[0072] Weigh 132 g of calcium chloride dihydrate, 10.2 g of magnesium chloride, 4.0 g of zinc chloride, and 8.1 g of ferric chloride hexahydrate and dissolve them in 2 L of deionized water. Stir until they are completely dissolved to form a yellow transparent solution.
[0073] The above two solutions were mixed while stirring, and a light yellow precipitate was formed after the mixing was completed. The temperature was gradually raised to 60°C and stirred for 1 hour, and then sealed and aged for 16 hours. Then centrifuged and washed with deionized water 6 times. The obtained usnic acid composite salt was then dried in a vacuum oven at 100°C, ground into fine powder by a high-speed wall breaking machine, and passed through a 200-mesh sieve to collect about 380g of the obtained micro-nano powder.
[0074] (2) Preparation of glycerophosphate complex salt: Weigh 345g of glycerophosphate and add it to 1L of deionized water (about 2.0M) to form a glycerophosphate solution. Stir 133g of calcium hydroxide, 12g of strontium hydroxide and 12.5g of zinc carbonate while adding. Continue stirring for 2 hours after adding. The pH is 7.3 at this time. Then seal and age for 16 hours. Then centrifuge and wash with deionized water 6 times. Then dry the obtained usnic acid complex salt in a vacuum oven at 80-120°C, grind it into fine powder with a high-speed wall breaker, and pass through a 200-mesh sieve to collect the obtained micro-nano powder.
[0075] (3) Preparation of sulfuric acid complex salt: Weigh 98g of concentrated sulfuric acid and slowly pour it along the wall into 1L of deionized water and stir evenly. Weigh 72.5g of calcium hydroxide and 1.3g of strontium hydroxide, add calcium hydroxide and strontium hydroxide to the sulfuric acid solution while stirring, stir for 2 hours, when the pH reaches 5.5, then seal and age for 12 hours. Then centrifuge, wash with deionized water 6 times, and then dry the obtained sulfuric acid complex salt in a vacuum oven at 100°C for 10 hours. The sulfuric acid complex salt is treated in water vapor at 140°C and 0.4MPa for 6 hours, then ground into fine powder by a high-speed wall breaker, and passed through a 200-mesh sieve to collect the obtained micro-nano powder.
[0076] (4) Preparation of usnic acid glycerophosphate sulfate complex salt bone repair material: Weigh 40 g of usnic acid complex salt prepared in (1), 80 g of glycerophosphate complex salt prepared in (2) and 80 g of sulfate complex salt prepared in (3) and mix them. The mixture is ball milled at 80-150 rpm. The ball milling chamber uses nitrogen to exhaust air. The ball milling chamber temperature is 40°C and the rotation speed is 200-300 r / hr. The ball milling time is 5 hours, and then the usnic acid glycerophosphate sulfate complex salt bone repair material powder with a particle size of less than 100 μm is obtained by sieving.
[0077] (5) Preparation of usnic acid glycerophosphate sulfate complex bone repair material implant: Mix 100 g of the usnic acid glycerophosphate sulfate complex bone repair material powder with 50 ml of pure water (water for injection), and stir thoroughly to mix: (1) directly inject the strip product by direct injection; (2) put it into a mold to make a test sample or shape it into the required shape, and sterilize it after natural curing for use.
[0078] 1: Preparation of test samples: Take 20 g of the usnic acid glycerophosphate sulfate complex bone repair material prepared in (4), add 10 ml of injection water, stir for 2 minutes, press into a porous polytetrafluoroethylene mold with a pore diameter of 6 mm and a height of 12 mm, eject after 5 minutes, and dry naturally in an environment with a temperature of 25°C and a humidity of 60%, and measure its curing time (the sample curing time is measured according to ISO9597-2008 standard using a Vicat instrument); start counting after the curing liquid is added to the sample powder, and end when the final setting needle (0.5 mm) of the Vicat instrument can no longer leave a mark on the sample surface. The calculated time is the final setting time of the bone cement; each sample is measured at least 5 times.
[0079] 2: Compression test method: Load speed 1mm / min:
[0080] Test the compressive strength after one day (1D), three days (3D) and five days (5D): After the sample (6 mm in diameter and 12 mm in height) was cured in air for 3 days, the mechanical strength of the sample was measured using a universal mechanical testing instrument, and each sample was measured at least 5 times.
[0081] 3: Degradation test method: Take the injection molded material and conduct degradation test in PBS solution: The preparation method of PBS is as follows; accurately weigh KH2PO4 (0.544g), Na2HPO4·12H2O (7.16g), NaCl (16g) and KCl (0.402g) and dissolve them in 2L deionized water, use a volumetric flask to make up the volume, and the pH measurement range is between 7.2-7.4; put the sample into a centrifuge tube and add a certain amount of PBS solution, the volume ratio of PBS solution to sample mass is 1g / 30mL; then place the centrifuge tube containing the sample in a constant temperature oscillating box at a temperature of 37℃ and a speed of 80rpm / min; take out the sample at 1 (1D), 1w, 4w, 12w and 24w days, weigh it and calculate the weight loss rate. Set up three control groups for each sample.
[0082] 4: pH determination: The supernatant of the sample was measured with a pH meter and PBS was replaced every 7 days.
[0083] 5: Cytotoxicity and cell proliferation rate test: Prepare the extraction solution in accordance with the provisions of T16886 on biological materials, and calculate the proliferation rate by comparing the standard extract with the blank.
[0084] 6: The usnic acid glycerophosphate sulfate complex bone repair material bone implant was implanted into the back of New Zealand white rabbits according to the requirements of T16886 to observe its biosafety such as degradation and inflammation in the body. The specific operation was to implant two 2.5g products into the muscles on both sides of the rabbit spine, with three rabbits in each group, and observe the effect. The operation was in accordance with the requirements of T16886.
[0085] Test results:
[0086] Setting time: 20min.
[0087] Compression strength: 1D: 12.5MPa; 3D: 22.2MPa, 5D: 3.4MPa.
[0088] Degradation results: 1D: 10.0%; 1w: 21.%; 4w: 40.4%; 12w: 85.3%; 24w: 100%.
[0089] pH value changes: 1D: 7.05, 1w: 7.11: 4w: 7.31; 12w: 7.29; 24w: 7.33.
[0090] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 126% compared with the blank, and the proliferation rate was 139% after dilution; compared with the blank, i.e., culture medium, the extract of glyceryl phosphate sulfate complex bone repair material bone implant can provide more nutrition, cell differentiation and proliferation.
[0091] After the wound surgery: there was no redness, swelling, exudation or fluid accumulation on the 1st day, 1st week and 4th week. The wound was basically healed in 1 week and completely healed in 4 weeks.
[0092] Example 2 (same as Example 1, except that the metal salt used in the preparation of the usnic acid composite salt is different from that in Example 1, and zinc chloride is removed)
[0093] (1) Preparation of usnic acid complex salt: 82 g of sodium hydroxide was dissolved in 2 L of deionized water, and after stirring until completely dissolved, 344 g of usnic acid was added, and the temperature was gradually raised to 60° C. while stirring until completely dissolved, to form a transparent usnic acid sodium salt solution. The soluble usnic acid solution obtained above was directly used as a raw material for preparing usnic acid complex salt.
[0094] Weigh 137 g of calcium chloride dihydrate, 10.2 g of magnesium chloride, and 8.1 g of ferric chloride hexahydrate and dissolve them in 2 L of deionized water. Stir until they are completely dissolved to form a yellow transparent solution.
[0095] The above two solutions were mixed while stirring, and a light yellow precipitate was formed after the mixing was completed. The temperature was gradually raised to 60°C and stirred for one hour, and then sealed and aged for 16 hours. Then centrifuged and washed with deionized water for 6 times. The obtained usnic acid composite salt was then dried in a vacuum oven at 100°C, ground into fine powder by a high-speed wall breaking machine, and passed through a 200-mesh sieve to collect about 379g of the obtained micro-nano powder.
[0096] (2)-(5) are the same as in Example 1.
[0097] Test results:
[0098] Setting time: 20min.
[0099] Compression strength: 1D: 11.6MPa; 3D: 20.5MPa, 5D: 28.8MPa.
[0100] Degradation results: 1D: 9.4%; 1w: 20.1%; 4w: 38.9%; 12w: 83.7%; 24w: 100%.
[0101] pH value changes: 1D: 7.11, 1w: 7.20: 4w: 7.33; 12w: 7.34; 24w: 7.33.
[0102] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 131% compared with the blank, and the proliferation rate was 143% after dilution; compared with the blank, i.e., culture medium, the extract of glyceryl phosphate sulfate complex bone repair material bone implant can provide more nutrition, cell differentiation and proliferation.
[0103] After the wound surgery: there was no redness, swelling, exudation or fluid accumulation on the 1st day, 1st week and 4th week. The wound was basically healed in 1 week and completely healed in 4 weeks.
[0104] Example 3 (same as Example 1, the metal salt used in the preparation of usnic acid composite salt is different from that in Example 1, and ferric chloride is removed)
[0105] (1) Preparation of usnic acid complex salt: 82 g of sodium hydroxide was dissolved in 2 L of deionized water, and after stirring until completely dissolved, 344 g of usnic acid was added, and the temperature was gradually raised to 60° C. while stirring until completely dissolved, to form a transparent usnic acid sodium salt solution. The soluble usnic acid solution obtained above was directly used as a raw material for preparing usnic acid complex salt.
[0106] Weigh 135 g of calcium chloride dihydrate, 10.2 g of magnesium chloride, and 4.0 g of zinc chloride and dissolve them in 2 L of deionized water. Stir until they are completely dissolved to form a colorless transparent solution.
[0107] The above two solutions were mixed while stirring, and a light white precipitate was formed after the mixing was completed. The temperature was gradually raised to 60°C and stirred for one hour, and then sealed and aged for 16 hours. Then centrifuged and washed with deionized water for 6 times. The obtained usnic acid composite salt was then dried in a vacuum oven at 100°C, ground into fine powder by a high-speed wall breaking machine, and passed through a 200-mesh sieve to collect about 377g of the obtained micro-nano powder.
[0108] (2)-(5) are the same as in Example 1.
[0109] Test results:
[0110] Setting time: 26min.
[0111] Compression strength: 1D: 10.2MPa; 3D: 18.7MPa, 5D: 25.1MPa.
[0112] Degradation results: 1D: 10.9%; 1w: 22.7%; 4w: 34.4%; 12w: 88.4%; 24w: 100%.
[0113] pH value changes: 1D: 7.13, 1w: 7.23: 4w: 7.34; 12w: 7.31; 24w: 7.33.
[0114] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 131% compared with the blank, and the proliferation rate was 143% after dilution; compared with the blank, i.e., culture medium, the extract of glyceryl phosphate sulfate complex bone repair material bone implant can provide more nutrition, cell differentiation and proliferation.
[0115] After the wound surgery: there was no redness, swelling, exudation or fluid accumulation on the 1st day, 1st week and 4th week. The wound was basically healed in 1 week and completely healed in 4 weeks.
[0116] Example 4 (same as Example 1, the composition of the glycerophosphate complex salt is different, and strontium hydroxide is removed)
[0117] (1) Same as Example 1
[0118] (2) Preparation of glycerophosphate complex salt: Weigh 345g of glycerophosphate and add it to 1L of deionized water (about 2.0M) to form a glycerophosphate solution. Add 140g of calcium hydroxide and 12.5g of zinc carbonate while stirring. Continue stirring for 2 hours after the addition. The pH is 7.3 at this time. Then seal and age for 16 hours. Then centrifuge and wash with deionized water 6 times. Then dry the obtained usnic acid complex salt in a vacuum oven at 80-120°C, grind it into fine powder with a high-speed wall breaker, pass through a 200-mesh sieve, and collect about 200g of the obtained micro-nano powder.
[0119] (3)-(5) are the same as in Example 1.
[0120] Test results:
[0121] Setting time: 20min.
[0122] Compression strength: 1D: 9.4MPa; 3D: 17.3MPa, 5D: 29.4MPa.
[0123] Degradation results: 1D: 11.3%; 1w: 23.5%; 4w: 41.9%; 12w: 86.4%; 24w: 100%.
[0124] pH value changes: 1D: 7.01, 1w: 7.05: 4w: 7.25; 12w: 7.31; 24w: 7.33.
[0125] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 131% compared with the blank, and the proliferation rate was 153% after dilution; compared with the blank, i.e., culture medium, the extract of glyceryl phosphate sulfate complex bone repair material bone implant can provide more nutrition, cell differentiation and proliferation.
[0126] After the wound surgery: there was no redness, swelling, exudation or fluid accumulation on the 1st day, 1st week and 4th week. The wound was basically healed in 1 week and completely healed in 4 weeks.
[0127] Example 5 (same as Example 1, the composition of the glycerophosphate complex salt is different, zinc carbonate is removed)
[0128] (1) Same as Example 1
[0129] (2) Preparation of glycerophosphate complex salt: Weigh 345g of glycerophosphate and add it to 1L of deionized water (about 2.0M) to form a glycerophosphate solution. Stir 140g of calcium hydroxide and 12g of strontium hydroxide while adding. Continue stirring for 2 hours after adding. The pH is 7.3 at this time. Then seal and age for 16 hours. Then centrifuge and wash 6 times with deionized water. Then dry the obtained usnic acid complex salt in a vacuum oven at 80-120°C, grind it into fine powder with a high-speed wall breaker, pass through a 200-mesh sieve, and collect about 199g of the obtained micro-nano powder.
[0130] (3)-(5) are the same as in Example 1.
[0131] Test results:
[0132] Setting time: 18min.
[0133] Compression strength: 1D: 10.1MPa; 3D: 19.4MPa, 5D: 31.7MPa.
[0134] Degradation results: 1D: 10.5%; 1w: 22.9%; 4w: 43.4%; 12w: 88.2%; 24w: 100%.
[0135] pH value changes: 1D: 7.10, 1w: 7.21, 4w: 7.28; 12w: 7.33; 24w: 7.33.
[0136] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract is 128% compared with the blank, and the proliferation rate is 145% after dilution; compared with the blank, i.e., culture medium, the extract of glyceryl phosphate sulfate complex bone repair material bone implant can provide more nutrition, cell differentiation and proliferation.
[0137] After the wound surgery: there was no redness, swelling, exudation or fluid accumulation on the 1st day, 1st week and 4th week. The wound was basically healed in 1 week and completely healed in 4 weeks.
[0138] Example 6 (same as Example 1, with different composition of sulfate composite salt and strontium hydroxide removed)
[0139] (1)-(2) Same as Example 1.
[0140] (3) Preparation of sulfuric acid complex salt: Weigh 98g of concentrated sulfuric acid and slowly pour it along the wall into 1L of deionized water and stir evenly. Weigh 74g of calcium hydroxide and add calcium hydroxide to the sulfuric acid solution while stirring for 2 hours. When the pH reaches 5.5, seal and age for 12 hours. Then centrifuge and wash with deionized water 6 times, and then dry the obtained sulfuric acid complex salt in a vacuum oven at 100°C for 10 hours. The sulfuric acid complex salt is treated in water vapor at 140°C and 0.4MPa for 6 hours, and then ground into fine powder by a high-speed wall breaking machine, and sieve through a 200-mesh sieve to collect 155g of the obtained micro-nano powder.
[0141] (4)-(5) Same as Example 1.
[0142] Test results:
[0143] Setting time: 22min.
[0144] Compression strength: 1D: 12.5MPa; 3D: 22.2MPa, 5D: 33.4MPa.
[0145] Degradation results: 1D: 10.0%; 1w: 21.%; 4w: 40.4%; 12w: 85.3%; 24w: 100%.
[0146] pH value changes: 1D: 7.05, 1w: 7.11: 4w: 7.31; 12w: 7.29; 24w: 7.33.
[0147] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 126% compared with the blank, and the proliferation rate was 139% after dilution; compared with the blank, i.e., culture medium, the extract of glyceryl phosphate sulfate complex bone repair material bone implant can provide more nutrition, cell differentiation and proliferation.
[0148] After the wound surgery: there was no redness, swelling, exudation or fluid accumulation on the 1st day, 1st week and 4th week. The wound was basically healed in 1 week and completely healed in 4 weeks.
[0149] Example 7 (same as Example 1, but different composition of sulfate composite salt, different content of strontium hydroxide from that of Example 1)
[0150] (1)-(2) Same as Example 1.
[0151] (3) Weigh 98g of concentrated sulfuric acid and slowly pour it along the wall into 1L of deionized water and stir evenly. Weigh 72.0g of calcium hydroxide and 1.8g of strontium hydroxide, add calcium hydroxide and strontium hydroxide to the sulfuric acid solution while stirring, stir for 2 hours, when the pH reaches 6.0, then seal and age for 12 hours. Then centrifuge, wash with deionized water 6 times, and then dry the obtained sulfuric acid complex in a vacuum oven at 100℃ for 10 hours. The sulfuric acid complex is treated in water vapor at 140℃ and 0.4MPa for 6 hours, then ground into fine powder by a high-speed wall breaker, and sieve through a 200-mesh sieve to collect 156g of the obtained micro-nano powder.
[0152] (4)-(5) Same as Example 1.
[0153] Test results:
[0154] Setting time: 19min.
[0155] Compression strength: 1D: 11.9MPa; 3D: 23.8MPa, 5D: 32.2MPa.
[0156] Degradation results: 1D: 9.4%; 1w: 18.7%; 4w: 38.5%; 12w: 81.2%; 24w: 100%.
[0157] pH value changes: 1D: 7.11, 1w: 7.23: 4w: 7.32; 12w: 7.35; 24w: 7.34.
[0158] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 128% compared with the blank, and the proliferation rate was 144% after dilution; compared with the blank, i.e., culture medium, the usnic acid glycerophosphate sulfate complex bone repair material bone implant extract can provide more nutrition, cell differentiation and proliferation.
[0159] After the wound surgery: there was no redness, swelling, exudation or fluid accumulation on the 1st day, 1st week and 4th week. The wound was basically healed in 1 week and completely healed in 4 weeks.
[0160] Example 8 (Compared to Example 1, the ratio of the three composite salts is different)
[0161] (1)-(3) are the same as in Example 1.
[0162] (4) Preparation of usnic acid glycerophosphate sulfate complex salt bone repair material: Weigh 30 g of usnic acid complex salt prepared in (1), 90 g of glycerophosphate complex salt prepared in (2) and 80 g of sulfate complex salt prepared in (3) and mix them. The mixture is ball-milled at 80-150 rpm. The ball-milling chamber uses nitrogen to exhaust air. The ball-milling chamber temperature is 40°C and the rotation speed is 200-300 r / hr. The ball-milling time is 5 hours, and then the powder of usnic acid glycerophosphate sulfate complex salt bone repair material with a particle size of less than 100 μm is obtained by sieving.
[0163] (5) Same as Example 1
[0164] Test results:
[0165] Setting time: 21min.
[0166] Compression strength: 1D: 12.7MPa; 3D: 24.9MPa, 5D: 33.4MPa.
[0167] Degradation results: 1D: 12.3%; 1w: 23.5%; 4w: 43.6%; 12w: 85.7%; 24w: 100%.
[0168] pH value changes: 1D: 7.20, 1w: 7.32: 4w: 7.35; 12w: 7.34; 24w: 7.35.
[0169] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 133% compared with the blank, and the proliferation rate was 146% after dilution; compared with the blank, i.e., culture medium, the usnic acid glycerophosphate sulfate complex bone repair material bone implant extract can provide more nutrition, cell differentiation and proliferation.
[0170] After the wound surgery: there was no redness, swelling, exudation or fluid accumulation on the 1st day, 1st week and 4th week. The wound was basically healed in 1 week and completely healed in 4 weeks.
[0171] Example 9 (Compared to Example 1, the ratio of the three composite salts is different)
[0172] (1)-(3) are the same as in Example 1.
[0173] (4) Preparation of usnic acid glycerophosphate sulfate complex salt bone repair material: Weigh 30 g of usnic acid complex salt prepared in (1), 80 g of glycerophosphate complex salt prepared in (2) and 90 g of sulfate complex salt prepared in (3) and mix them. The mixture is ball milled at 80-150 rpm. The ball milling chamber uses nitrogen to exhaust air. The ball milling chamber temperature is 40°C and the rotation speed is 200-300 r / hr. The ball milling time is 5 hours, and then the usnic acid glycerophosphate sulfate complex salt bone repair material powder with a particle size of less than 100 μm is obtained by sieving.
[0174] (5) Same as Example 1
[0175] Test results:
[0176] Setting time: 17min.
[0177] Compression strength: 1D: 13.6MPa; 3D: 26.3MPa, 5D: 35.7MPa.
[0178] Degradation results: 1D: 11.4%; 1w: 22.6%; 4w: 44.5%; 12w: 83.7%; 24w: 100%.
[0179] pH value changes: 1D: 7.20, 1w: 7.32: 4w: 7.35; 12w: 7.34; 24w: 7.35.
[0180] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 132% compared with the blank, and the proliferation rate was 145% after dilution; compared with the blank, i.e., culture medium, the usnic acid glycerophosphate sulfate complex bone repair material bone implant extract can provide more nutrition, cell differentiation and proliferation.
[0181] After the wound surgery: there was no redness, swelling, exudation or fluid accumulation on the 1st day, 1st week and 4th week. The wound was basically healed in 1 week and completely healed in 4 weeks.
[0182] Example 10 (different from Example 1, the solidifying liquid is physiological saline)
[0183] (1)-(4) are the same as in Example 1.
[0184] (5) Preparation of usnic acid glycerophosphate sulfate complex bone repair material implant: Mix 100 g of the usnic acid glycerophosphate sulfate complex bone repair material powder with 50 ml of normal saline (0.9% sodium chloride aqueous solution), and stir thoroughly to mix: (1) directly inject the strip product by direct injection; (2) put it into a mold to make a test sample or shape it into the required shape, and sterilize it after natural curing for use.
[0185] Test results:
[0186] Setting time: 28min.
[0187] Compression strength: 1D: 9.7MPa; 3D: 21.5MPa, 5D: 29.4MPa.
[0188] Degradation results: 1D: 12.2%; 1w: 23.8%; 4w: 45.4%; 12w: 84.3%; 24w: 100%.
[0189] pH value changes: 1D: 7.15, 1w: 7.22: 4w: 7.285; 12w: 7.31; 24w: 7.335.
[0190] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 127% compared with the blank, and the proliferation rate was 133% after dilution; compared with the blank, i.e., culture medium, the usnic acid glycerophosphate sulfate complex bone repair material bone implant extract can provide more nutrition, cell differentiation and proliferation.
[0191] After the wound surgery: there was no redness, swelling, exudation or fluid accumulation on the 1st day, 1st week and 4th week. The wound was basically healed in 1 week and completely healed in 4 weeks.
[0192] Comparative Example 1: Calcium Glycerophosphate
[0193] Preparation of oil-phosphate complex salt: Weigh 345g of glycerophosphoric acid (172.07), add it to 1L of deionized water (about 2.0M) to form a glycerophosphoric acid solution, stir while adding 148g of calcium hydroxide, continue stirring for 2 hours after adding, and the pH is 7.3. Then seal and age for 16 hours. Then centrifuge and wash with deionized water 6 times. Then dry in a vacuum oven at 100°C, grind into fine powder by a high-speed wall breaker, pass through a 200-mesh sieve, and collect the resulting micro-nano powder of about 180g.
[0194] Test: It is difficult to solidify, and the 1D compressive strength is only 1.3MPa. It collapses after being added to PBS for 10 minutes, and the degradation and biological performance evaluation cannot be carried out.
[0195] Comparative Example 2: Calcium Phosphate
[0196] Take 20g of calcium phosphate powder, add 10ml of water for injection and stir into a paste, blend evenly, and put the blended product into a mold to make a test sample.
[0197] After being placed in simulated body fluid, it completely disintegrated within 6 hours and could not proceed to the next step of testing.
[0198] Comparative Example 3: Calcium Sulfate
[0199] Take 20g of calcium sulfate hemihydrate powder, add 10ml of water for injection and stir into a paste, blend evenly, and put the blended product into a mold to make a test sample.
[0200] Setting time: 5min.
[0201] Compression strength: 1D: 12MPa; 3D: 21MPa, 5D: 35MPa.
[0202] Degradation results: 1D: 14.4%; 1w: 24.6%; 4w: 63.4%; 12w: 100%;
[0203] pH value changes: 1D: 5.21, 1w: 5.63: 4w: 5.65; 12w: 6.65.
[0204] Cytotoxicity and cell proliferation rate: Level 1; the proliferation rate of the standard extract is 90% compared with the blank.
[0205] After wound surgery: 1 day, 1 week, 4 weeks, and 12 weeks, the incidence of redness, swelling, exudation, and fluid accumulation was 13%.
[0206] Comparative Example 4: Same as Example 1, except that the usnic acid complex salt is removed.
[0207] Weigh 50 g of the glycerophosphate complex salt prepared in (2) and 50 g of the sulfate complex salt prepared in (3) and mix them. The mixture is ball-milled at 80-150 rpm. The ball-milling chamber uses nitrogen to exhaust air. The ball-milling chamber temperature is 40° C. and the rotation speed is 200-300 r / hr. The ball-milling time is 5 hours. After that, the powder of the glycerophosphate sulfate complex salt bone repair material with a size of less than 100 μm is obtained by sieving.
[0208] Test results:
[0209] Setting time: 25min.
[0210] Compression strength: 1D: 8.5MPa; 3D: 20.2MPa, 5D: 28.1MPa.
[0211] Degradation results: 1D: 16.3%; 1w: 27.5%; 4w: 48.9%; 12w: 88.6%; 24w: 100%.
[0212] pH value changes: 1D: 6.85, 1w: 7.01: 4w: 7.12; 12w: 7.21; 24w: 7.23.
[0213] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 113% compared with the blank, and the proliferation rate was 121% after dilution; compared with the blank, i.e., culture medium, the glycerol phosphate sulfate complex bone repair material bone implant extract can provide more nutrition, cell differentiation and proliferation.
[0214] After the wound surgery: 1 rabbit had redness and swelling in the wound on day 1, 1 rabbit had redness and swelling in the wound on week 1 and 4, and 1 rabbit had exudate, the wound was mostly healed in week 1, and completely healed in week 4. After removing the usnic acid composite salt, there was a big difference compared with Example 1.
[0215] Comparative Example 5: Same as Example 1, except that the glycerophosphate complex salt is removed.
[0216] Weigh 30 g of the usnic acid complex salt prepared in (1) and 70 g of the sulfate complex salt prepared in (3) and mix them. The mixture is ball-milled at 80-150 rpm, the ball-milling chamber uses nitrogen to exhaust air, the ball-milling chamber temperature is 40° C., and the rotation speed is 200-300 r / hr. The ball-milling time is 5 hours, and then the usnic acid sulfate complex salt bone repair material powder with a size of less than 100 μm is sieved.
[0217] Test results:
[0218] Setting time: 20min.
[0219] Compression strength: 1D: 11.2MPa; 3D: 22.6MPa, 5D: 29.4MPa.
[0220] Degradation results: 1D: 11.1%; 1w: 20.3%; 4w: 44.4%; 12w: 81.3%; 24w: 98.8%.
[0221] pH value changes: 1D: 7.01, 1w: 7.13: 4w: 7.22; 12w: 7.31; 24w: 7.34.
[0222] Cytotoxicity and cell proliferation rate: Level 0; the proliferation rate of the standard extract was 106% compared with the blank, and the proliferation rate after dilution was 112%; compared with the blank culture medium, the usnic acid sulfate complex salt bone repair material bone implant extract can provide more nutrition, cell differentiation and proliferation. However, compared with Example 1, the cell activity and compatibility are about 20%.
[0223] After the wound surgery: there was no redness, swelling, exudation or fluid accumulation on the 1st day, 1st week and 4th week. The wound was basically healed in 1 week and completely healed in 4 weeks.
[0224] Comparative Example 6: Same as Example 1, except that the sulfate complex salt is removed.
[0225] 30 g of the usnic acid complex salt prepared in (1) and 70 g of the glycerophosphate complex salt prepared in (2) were weighed and mixed, and the mixture was ball-milled at 80-150 rpm, the ball-milling chamber was exhausted with nitrogen, the ball-milling chamber temperature was 40° C., and the rotation speed was 200-300 r / hr. The ball-milling time was 5 hours, and then the usnic acid glycerophosphate composite bone repair material powder with a size of less than 100 μm was obtained by sieving.
[0226] Take 20g of the usnic acid glycerol phosphate composite bone repair material powder, add 10ml of injection water and stir into a paste, blend evenly, and put the blended product into a mold to make a test sample.
[0227] Test: It is difficult to solidify, and the 1D compressive strength is only 1.3MPa. It collapses after being added to PBS for 10 minutes, and the degradation and biological performance evaluation cannot be carried out.
[0228] After being placed in simulated body fluid, it completely disintegrated within 6 hours and could not proceed to the next step of testing.
[0229] It should be noted that the preferred embodiments of the present invention are given in the specification of the present invention, but the present invention can be implemented in many different forms and is not limited to the embodiments described in this specification. These embodiments are not intended to be additional limitations on the content of the present invention. The purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. In addition, the above-mentioned technical features continue to be combined with each other to form various embodiments not listed above, which are all considered to be within the scope of the present invention specification; further, for ordinary technicians in this field, they can be improved or transformed according to the above description, and all these improvements and transformations should belong to the protection scope of the claims attached to the present invention.
Claims
1. A bone repair material based on a salt of usnic acid, glycerophosphoric acid and sulfuric acid, characterized in that: The bone repair material comprises component A, component B and component C, The component A is a composite salt of usnic acid, calcium, and optionally other trace metal elements that promote bone tissue regeneration or are required by the human body. The component B is a composite salt of glycerophosphate, calcium, and optionally other trace metal elements that promote bone tissue regeneration or are required by the human body. The component C is a composite salt of sulfuric acid, calcium, and optionally other trace metal elements that promote bone tissue regeneration or are required by the human body.
2. The bone repair material according to claim 1, characterized in that: The mass ratio of component A, component B and component C is 10-30:40-50:30-40.
3. The bone repair material according to claim 1, characterized in that: The molar ratio of calcium to other trace metal elements in component A is 80-90:10-20; Further, the other trace metal elements in component A include at least one of magnesium, strontium, zinc and iron; Furthermore, the molar ratio of calcium to other trace metal elements in component B is 80-90:10-20; Further, the other trace metal elements in component B do not include magnesium, and preferably include at least one of strontium, zinc and iron; Further, the molar ratio of calcium to other trace metal elements in component C is 95-100:0-5; Furthermore, the other trace metal elements in component C do not include magnesium, zinc and iron, and preferably include strontium.
4. A bone cement based on a salt of usnic acid, glycerophosphoric acid and sulphuric acid, characterised in that A bone repair material and a curing liquid based on a salt of usnic acid, glycerophosphate and sulfuric acid as claimed in any one of claims 1 to 3, comprising a solid-liquid ratio of 1.0:0.2-1.5 (g:ml); Furthermore, the bone cement can be directly used to be injected into the desired wound or defect site through an injection device, or can be loaded into a mold to be made into a test sample or molded into a desired shape; Furthermore, the solidifying liquid is selected from at least one of water for injection, physiological saline or glucose injection.
5. A method for preparing a bone repair material based on a salt of usnic acid, glycerophosphate and sulfate according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) firstly reacting usnic acid with a strong base to prepare soluble usnic acid salt, and then reacting the obtained soluble usnic acid salt with calcium and optionally soluble salts of other trace metal elements that promote bone tissue regeneration or are required by the human body to obtain the component A; (2) reacting glycerophosphate with calcium and optionally carbonates, oxides and / or hydroxides of other trace metal elements that promote bone tissue regeneration or are required by the human body to obtain the component B; (3) reacting sulfuric acid with calcium and optionally carbonates, oxides and / or hydroxides of other trace metal elements that promote bone tissue regeneration or are required by the human body to obtain the component C; (4) Component A, component B and component C are mixed and then ball-milled to obtain the bone repair material based on the salt of usnic acid, glycerophosphate and sulfuric acid.
6. The method according to claim 5, characterized in that The molar ratio of the strong base to usnic acid in step (1) is 2.0-2.5:1.0; Further, the strong base includes at least one of lithium hydroxide, sodium hydroxide, and potassium hydroxide; Furthermore, in step (1), the molar ratio of the calcium element and optionally the soluble salt of other trace metal elements that promote bone tissue regeneration or are required by the human body to the soluble usnic acid salt is 1.0-2.0:1.0; Further, the soluble salt of calcium and optionally other trace metal elements that promote bone tissue regeneration or are required by the human body includes at least one of calcium nitrate, magnesium nitrate, strontium nitrate, zinc nitrate, iron nitrate, calcium chloride, magnesium chloride, strontium chloride, zinc chloride, iron chloride, magnesium sulfate, zinc sulfate, and iron sulfate; Furthermore, the molar ratio of calcium to other trace metal elements in the soluble salt of calcium and optionally other trace metal elements that promote bone tissue regeneration or are required by the human body is 80-90:10-20; Further, the molar ratio of calcium, magnesium, zinc and iron in the soluble salt of calcium and optionally other trace metal elements that promote bone tissue regeneration or are required by the human body is: 80-90:10-5:5-3:5-2; Furthermore, step (1) comprises stirring usnic acid and a strong base in water at 50-80°C for 0.5-2h, then adding an aqueous solution of calcium and optionally a soluble salt of other trace metal elements that promote bone tissue regeneration or are required by the human body, and stirring at 50-80°C for 0.5-2h, then sealing and aging for 12-24 hours, centrifuging the precipitate, and obtaining component A after washing, drying and crushing.
7. The method according to claim 5, characterized in that The calcium element and optionally carbonates, oxides and / or hydroxides of other trace metal elements that promote bone tissue regeneration or are required by the human body in step (2) include at least one of calcium carbonate, strontium carbonate, zinc carbonate, iron carbonate, calcium oxide, strontium oxide, zinc oxide, ferric oxide, calcium hydroxide, strontium hydroxide, zinc hydroxide and iron hydroxide; Furthermore, in step (2), the molar ratio of calcium to other trace metal elements in the carbonate, oxide and / or hydroxide of the calcium element and optionally other trace metal elements that promote bone tissue regeneration or are required by the human body is 80-90:20-10; Furthermore, step (2) comprises dissolving glycerophosphate in water, and then adding calcium and optionally carbonates, oxides and / or hydroxides of other trace metal elements that promote bone tissue regeneration or are required by the human body under stirring until the pH of the solution reaches 7.0-7.5, stirring for 1-3 hours, and then sealing and aging for 12-24 hours, centrifuging and separating the precipitate, washing, drying and crushing to obtain the component B.
8. The method according to claim 5, characterized in that The calcium element and optionally carbonates, oxides and / or hydroxides of other trace metal elements that promote bone tissue regeneration or are required by the human body in step (3) include at least one of calcium carbonate, strontium carbonate, calcium oxide, strontium oxide, calcium hydroxide and strontium hydroxide; Furthermore, in step (3), the calcium element and optionally the carbonate, oxide and / or hydroxide of other trace metal elements that promote bone tissue regeneration or are required by the human body have a molar ratio of calcium to strontium of 95-100:0-5; Further, step (3) comprises preparing a 1.0-2.0M sulfuric acid aqueous solution, and then adding calcium and optionally carbonates, oxides and / or hydroxides of other trace metal elements that promote bone tissue regeneration or are required by the human body under stirring until the pH of the solution reaches 5.5-6.0, stirring for 1-3 hours, and then sealing and aging for 12-24 hours, centrifuging and separating the precipitate, washing, drying, steaming, and crushing to obtain the component B; Furthermore, the water vapor treatment is carried out in water vapor at 120-150° C. and 0.2-1 MPa for 3-12 hours.
9. The method according to claim 5, characterized in that The mass ratio of component A, component B and component C in step (4) is 10-30:40-50:30-40; Furthermore, the ball milling in step (4) is carried out under nitrogen protection, the temperature of the ball milling chamber is not higher than 60° C., the rotation speed is 200-300 r / hr, and the ball milling time is 2-8 hours; Furthermore, step (4) comprises ball milling and then sieving to obtain the bone repair material based on the salt of usnic acid, glycerophosphate and sulfuric acid with a particle size of less than 100 μm.
10. The method according to claim 5, characterized in that The method further comprises mixing the bone repair material based on the salt of usnic acid, glycerophosphate and sulfuric acid obtained in step (4) with a solidifying liquid at a solid-liquid ratio of 1.0:0.2-1.5 (g:ml), and blending them uniformly to obtain bone cement, which can be directly used for injection into the desired wound or defect site through an injection device, or can be loaded into a mold to make a test sample or molded into a desired shape; Furthermore, the solidifying liquid is selected from at least one of water for injection, physiological saline or glucose injection.
